Implications of the Constitutional Court Decision Number 91/Puu-Xviii/2020 Toward Job Creation Law in The Mineral and Coal Mining Sector - Lelisari, Lelisari; Tanjung, Ridho Aulia; Pakpahan, Zainal Abidin; Imawanto, Imawanto; Hamdi, Hamdi (Magister of Law, Faculty of Law, University of Mataram, 2022)
This study aims to analyze and examine the juridical implications of the decision of Constitutional Court Number 91/PUU XVII/2020 on the job creation law in the mineral and coal mining sector. The research method used is a normative legal research method with approach legislation. The results illustrate that the juridical implication of the Job Creation Act in the mineral and coal mining sector is that in its decision the Constitutional Court stated that the Job Creation Act was still valid as long as the law-makers made improvements in the procedures for establishing Job Creation Law. In this case, the Constitutional Court has given two years for the legislators to revise the procedure for the formation of the Job Creation Law since the decision was pronounced. If no improvements are made, the Law can be declared unconstitutional permanently. Thus, if Law Number 11 of 2020 concerning job creation is unconstitutional, namely permanently removing coal incentive opportunities, the elimination of coal incentive opportunities must indeed be carried out due to the targets of coal utilization in Article 128A, not power optimization towards clean energy and will increase the portion of coal in the national energy mix and overall will systematically overlap with climate adaptation and mitigation targets and programs as well as the Articles in the Job Creation Act are also infiltrated by the interests of mining and dirty energy businesses.